An Analysis of Teacher’s Strategy in Teaching Speaking at SMA Negeri 9 Haltim - Syamsia; Junaidi Hamdi (ITScience (Information Technology and Science), 2022)
This research is aimed at describing the strategies used by the English teacher of the students of SMA Negeri 9 Haltim in teaching speaking. Based on pre-observation, the researcher found that SMA Negeri 9 Haltim applied teaching strategies in the teaching and learning process, especially in speaking and it makes the students easier to understand speaking English. This study was conducted by using a descriptive qualitative design. The subjects of this research were the English teacher and the students of SMA Negeri 9 Haltim. The data was gained by observation, interview, and documentation. The results indicated that there are five strategies in teaching speaking which applied by the English teacher. They are drilling, simulation and role play, the portrait interview, creative tasks, and group work. There were also two principles applied by the teacher to develop vocabulary mastery and fluency, the first is the activity is meaning-focused, and the second is the learners take a part in activities where all the language items are within their previous experiences. The teacher applied those strategies to help the students become active so that they can understand the lessons and also enjoy the teaching and learning process.